THE PAI PRODUCT AIK CURRICULUM'S RELEVANCE TO THE ISMUBA CURRICULUM NEEDS FOR MIDDLE SCHOOLS IN MEDAN CITY - Nurzannah; Munawir Pasaribu; Hasanuddin; Isthifa Kemal (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
The purpose of this study is to ascertain the following: the content of the ISMUBA curriculum for Muhammadiyah Middle Schools in Medan City, the content of the AIK curriculum utilized in the UMSU PAI study program, and the relevance of the AIK curriculum content of the PAI UMSU study program to the requirements of the ISMUBA SMP Muhammadiyah school in Medan City. This kind of study is qualitative and employs focus groups, content analysis, and interview techniques. The study's findings indicate that the first four courses in the AIK PAI UMSU curriculum are Islamic Science and Technology, Muhammadiyahan; Worship and Mu'amalah; and Religious Education (al-Islam). Second, there is a wide range of subjects in the ISMUBA curriculum for Muhammadiyah Middle Schools in Medan City, including both Al-Islamic and Muhammadiyah instruction. Meanwhile, the 2013 SMP/MT curriculum is used in Arabic language instruction; however, the learning materials used vary throughout schools. Third, on average, 65.5% of the material of the Ismuba curriculum (Al-Islam et al.) for Muhammadiyah Middle Schools in Medan City is relevant to the AIK subject of the PAI Study Program. Other courses provided to UMSU PAI Study Program students, such as Tahsin Al-Quran courses, History of Islamic Civilization, Insya' Muhadatsah, Tarbawi Tafsir, Tarbawi Hadith, Ushul Fiqh, and Contemporary Fiqh, augment the questionable relevance of the AIK content.